1975
DOI: 10.1037/h0076960
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic studies of aggressive behavior: Aggressive stimuli, victim visibility, and horn honking.

Abstract: Three studies extended laboratory research on aggression to a naturalistic setting which involved horn honking from drivers as a measure of aggression; the studies were adapted from Doob and Gross. The results from a survey (Study 1) of 59 drivers suggested that they were frequently irritated by and aggressive toward other drivers. A second study (using a 3 X 2 factorial design with 92 male drivers) indicated that manipulations of a rifle in an aggressive context and victim visibility (dehumanization) both sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
6

Year Published

1976
1976
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(82 citation statements)
references
References 18 publications
1
74
0
6
Order By: Relevance
“…For those subjects who accepted the negative feedback as genuine, GUNS/NO GUNS 307 response suppression might have occurred for a different reason. Turner et al (1975), in the horn-honking experiment described earlier, found that male drivers of older vehicles, and females, emitted fewer honks in the presence of a rifle and an aggressive bumper sticker. This is interpreted as inhibition of aggressive responding (horn-honking) toward a higher status person.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For those subjects who accepted the negative feedback as genuine, GUNS/NO GUNS 307 response suppression might have occurred for a different reason. Turner et al (1975), in the horn-honking experiment described earlier, found that male drivers of older vehicles, and females, emitted fewer honks in the presence of a rifle and an aggressive bumper sticker. This is interpreted as inhibition of aggressive responding (horn-honking) toward a higher status person.…”
Section: Resultsmentioning
confidence: 99%
“…Turner et al (1975), for example, actually found that male drivers of older vehicles, and female drivers of all vehicles, engaged in more horn-honking when no rifle or bumper sticker was present. Although these results are interpreted as reflecting inhibition produced by the rifle in an aggressive context, other interpretations are obviously possible.…”
mentioning
confidence: 99%
“…However, researchers who report gender differences in aggression tend to use experimental paradigms in which participants are not provoked (Lando, Johnson-Payne, Gilbert, & Deutsch, 1977). Yet, when the experimental paradigm includes a provocation before their opportunity to aggress, gender differences often are not found (e.g., Ahmed, 1982;Dor-Shav & Dolgin, 1981;Frodi, 1978;Golin & Romanowski, 1977;Turner, Layton, & Simons, 1975). Moreover, in several studies that vary both gender of participant and level of provocation, women exhibit less aggression than men under relatively neutral conditions but behave slightly more aggressively than men when provoked (e.g., Anderson, 1993;Fischer, Kelm, & Rose, 1969;Schuck, Schuck, Hallam, Mancini, & Wells, 1971;Taylor & Epstein, 1967).…”
mentioning
confidence: 99%
“…Subjects may give only desirable answers to the hypothetical situations described to them [33]. Also, high self-awareness magnifies the correlates between self-reports and behavior [34]. A meta-analysis has found a positive correlation between aggression, measured by self-reports, and personality dimensions [35].…”
Section: Discussionmentioning
confidence: 99%